Rice straw reinforce poly (latic acid) biopolymer. mechanical and thermal properties / Shuhaila Saindin - Saindin, Shuhaila (2020)
Poly(lactic) acid is currently a most potential and popular polymeric material, which will play a key role in building of a sustainable bioeconomy. Knowledge of biodegradation of PLA is crucial for treating plastic wastes and easing the serious energy crisis. The biodegradability of Poly(lactic) acid based on microorganisms (bacteria and fungus) and biochemical processes of degradation have been advanced in recent years. However, using 100 percent amount of Poly(lactic) acid to produce a plastic film need high cost and the plastic film tend to be brittle. Addition of natural fibre which is rice straw has reduced the cost as well as enhanced the strength of the film. The objectives of this study is to fabricate biopolymer Poly(lactic) acid reinforced with various ratio of RS namely 0, 10, 20, 30, and 40 (% w/w). Other than that, the aim of this study is to investigate thermal and mechanical properties of PLA/RS biopolymer by various testing such as Fourier Transform Infrared Analysis (FTIR), Differential Scanning Calorimeter (DSC), tensile, and water absorption test and as well as to analyse biodegradability of PLA/RS biopolymer by soil-degradability test. The result of FTIR distinctly showed that bonding of hydrogen present between the polymers can increase the toughness of the film. This bonding is presented at frequency 2996 cm-1 and 3500cm-1 which contributed to the hydrogen bonding. In this research the optimum fibre loading is 10% because it the higher value of tensile strength among others which is 15.11MPa. Other than that, the percent crystallinity of film with optimum rice straw fibre content is higher than neat Poly(lactic) acid film which is 253.80% as compared to 133.13%. The PLA/RS film also can withstand under modest to high temperature with the highest melting temperature (Tm) at 59.64°C and optimum glass temperature (Tg) at 152.08°C. Besides, the percentage of water intake of PLA/RS increased gradually with increment of RS fibre through the hydrophobicity property in RS fibre was lead to improvement in biodegradation.